The Effectiveness of Using Custom Made Soft Corset Model Towards Abdominal Circumference in Postpartum - Handayani, Sri; Rahmadani, Siti; Nurhayati, Nurhayati; Mahardhika, Dhanny Widhata (Women, Midwives and Midwifery, 2024)
Background: During the postpartum period, mothers often seek to maintain abdominal slimness by utilizing compression garments like stagen or bengkung. However, advancements in textile technology have led to a decline in the popularity of stagen, with corsets emerging as a preferred alternative due to their perceived practicality. Corsets, known for their flexible yet durable woven texture, serve as effective abdominal binders, aiding in both aesthetic preservation and posture Purpose: This study aimed to evaluate the effectiveness of custom-made soft corsets in reducing abdominal circumference among postpartum mothers. The findings are anticipated to offer insights into the comfort and efficacy of using these corset models to promote abdominal muscle tightening in postpartum individuals. Methods: The design is quasi-experimental. Data analysis includes univariate analysis in the form of respondent characteristic data and multivariate analysis with General Linear Model Repeated Measures (GLM RM). Results: The difference in average abdominal circumference in the intervention group decreased, namely in measurement I of 89.4 cm (SD = 8.56), measurement II of 77.67 (SD = 7.51) cm and measurement III of 69.67 cm (SD = 8.41), while low back pain of measurement I of 2.73 (SD = 0.46), measurement II of 1.80 (SD = 0.56) and measurement III of 0.40 (0.51). Conclusion: Custom made soft corset treatment for postpartum mothers proved to be more effective in reducing the size of abdominal circumference, namely in the results of the analysis of the interaction between the second and third measurements, seen from a steeper slope, and in low back pain measurements seen from a steeper slope between the first and second measurements.